2021
DOI: 10.3390/ijerph18030871
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnosed Depression and Self-Reported Depression Symptom as a Risk Factor of Periodontitis: Analysis of 2016–2018 Korean National Health and Nutrition Examination Survey Data

Abstract: Depression causes damage to the immune defense mechanism, and it can worsen periodontitis due to the accumulation of periodontitis pathogens. This study was conducted in order to explore the association of diagnosed depression and self-reported depression symptom with periodontitis by using the Korean National Health and Nutrition Examination Survey 7th (KNHANES VII) data. A total of 12,689 participants aged over 19 received a periodontal examination among the 24,269 participants of KNHANES VII. Diagnosed depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The same type of association was depicted regarding the prevalence of anxiety in patients affected by chronic inflammatory diseases, including periodontitis [27,28]. However, some contradictory results could be found within the scientific literature [29]. Such discrepancies could be explained by the specific type of population investigated and the use of different methods of psychological evaluation.…”
Section: Introductionmentioning
confidence: 75%
“…The same type of association was depicted regarding the prevalence of anxiety in patients affected by chronic inflammatory diseases, including periodontitis [27,28]. However, some contradictory results could be found within the scientific literature [29]. Such discrepancies could be explained by the specific type of population investigated and the use of different methods of psychological evaluation.…”
Section: Introductionmentioning
confidence: 75%
“…The work tension was significantly correlated with the chronic periodontitis 69 . Overload work activity possibly increase the tendency of developing depressive symptoms, which has a positive association with periodontitis 70–72 …”
Section: Discussionmentioning
confidence: 95%
“…69 Overload work activity possibly increase the tendency of developing depressive symptoms, which has a positive association with periodontitis. [70][71][72] Due to the cross-sectional nature of the study, unreliable causation and directionality between physical activity PA and periodontitis are the main shortcomings. Biases also exist.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of self-reported depression, secondary data, and use of different case definitions of periodontitis limit the validity of results of these studies. Further, a study reported that diagnosed depression, rather than self-reported depression, acts as a risk factor for periodontitis, [ 9 ]. On the contrary, some studies failed to show any relationship between psychosocial factors and periodontal status [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%